Relationship between Body Mask Index (BMI) and Titer C-Reactive Protein in Women - Hari Saktiningsih; Sulasmi; Mastuti Widi Lestari (Universitas Widya Gama Mahakam Samarinda, 2021)
Abstract Background: The prevalence of metabolic syndrome is certainly likely to increase with the increasing prevalence of obesity. A reliable indicator and easy-to-use for measuring body fat is body mass index (BMI), in the state of obesity there is a disruption of adiposity balance that is released and as an early marker of inflammation and triggers the formation of C-Reactive protein in the liver. Objectives: The goal of the study was to analyze the relationship between BMI and Titer C-Reactive Protein in women.. Research Metodes: This study is an observational analytical study with a cross sectional approach. The population in this study was women aged 25-65 years. A total of 39 samples were conducted in quota sampling. The data was analyzed with Kendal's tau non parametric test. Findings: The results of the study obtained a value of significance or Sig. (2-tailed) 0.908 > 0.05, This result states that there is no relationship between body mass index and titer C-Reactive protein. Correlation coefficient value is -0.015, express a very weak linear relationship. Negative values indicate the opposite direction of the relationship, where the higher the BMI, the lower the C-Reactive protein titer. Conclusion: Statistical test results obtained a value of p (0.908) > α (0.05), it states that no significant association between BMI and Titer C-Reactive Protein in women